The time course of injury risk after return-to-play in professional football (soccer) - Zhang, G.; Brink, M.; aus der Fünten, K.; Tröß, T.; Willeit, P.; Meyer, T.; Lemmink, K.; Hecksteden, A. (Sports Medicine, 2025)
Background:Injury risk in professional football (soccer) is increased in the weeks following return-to-play (RTP). However, the time course of injury risk after RTP (the hazard curve) as well as its influencing factors are largely unknown. This knowledge gap, which is arguably due to the volatility of instantaneous risk when calculated for short time intervals, impedes on informed RTP decision making and post-RTP player management. Objectives: This study aimed to characterize the hazard curve for non-contact time-loss injuries after RTP in male professional football and to investigate the influence of the severity of the index injury and playing position. Methods: Media-based injury records from the first German football league were collected over four seasons as previously published. Time-to-event analysis was employed for non-contact time-loss injury after RTP. The Kaplan-Meier survival function was used to calculate the cumulative hazard function, from which the continuous hazard function was retrieved by derivation. Results: There were 1623 observed and 1520 censored events from 646 players analyzed. The overall shape of the hazard curve was compatible with an exponential decline of injury risk, from an approximately two-fold level shortly after RTP towards baseline, with a half-time of about 4 weeks. Interestingly, the peak of the hazard curve was slightly delayed for moderate and more clearly for severe index injuries. Conclusions: The time course of injury risk after RTP (the hazard curve) can be characterized based on the Kaplan-Meier model. The shape of the hazard curve and its influencing factors are of practical as well as methodological relevance and warrant further investigation.